Exploring The Mughal Styles Of Colonial Mosque In Johor - Mohd Aliff Izuan Md Yasin; Athika Norlaili Abdul Halim; Nor Syahila Ab Rashid; Noor Hayati Ismail (Semarak Ilmu Publishing, 2026)
Non-Indexed Publication